Extension of Salam Leaf Tea Making Process for Family Welfare Development Mothers in Sei Alim Ulu Village - Pradana, Putra; Nasution, Rahmadani Sandra; Armanda, Akbar Agustama; Pramita, Desy; Syafitri, Nabila; Maharani, Dina (Jurnal Abdi Mas Adzkia, 2024)
Drinking tea or coffee is also a human culture or habit that has existed for a long time. Counselling on making tea from bay leaves to PKK mothers in Sei Alim Ulu village has been carried out smoothly. The aim of this service is to increase the understanding of Sei Alam Village Women in Making Bay Leaf Tea. The extension activity for making bay leaf tea was held on August 09, 2023, at the Sei Alim Ulu Village Hall Office Hall. This research uses an action research procedure (Action Research). Action research is a process that continuously alternates between inquiry and action, between application and innovative thinking. The researchers tried this action research using bay leaves in tea preparations by combining ginger and cinnamon recipes. This counselling is carried out to provide or transfer knowledge to mothers in the village that bay leaves can not only be used as spices in cooking and make business opportunities that can increase the income of Village-Owned Enterprises in the future. A suggestion for the public is to try combining bay leaf tea with other herbs such as ginger, turmeric or cinnamon to get more benefits. Not only does this combination provide a more enjoyable flavor, but it can also enhance its properties.